Structure of an arabinogalactan from the edible tropical fruit tamarillo (Solanum betaceum) and its antinociceptive activity. (13th February 2015) - do Nascimento, Georgia Erdmann; Corso, Claudia Rita; de Paula Werner, Maria Fernanda; Baggio, Cristiane Hatsuko; Iacomini, Marcello; Cordeiro, Lucimara M.C.
Highlights: A type I arabinogalactan was found in the pulp of tamarillo fruits. A highly-methoxylated homogalacturonan was also present. The type I arabinogalactan had a main chain branched only at O -6. It was showed an antinociceptive effect on inflammatory pain models. Abstract: A structural characterization of polysaccharides obtained by aqueous extraction of ripe pulp of the edible exotic tropical fruit named tamarillo ( Solanum betaceum ) was carried out. After fractionation by freeze–thaw and α-amylase treatments, a fraction containing a mixture of highly-methoxylated homogalacturonan and of arabinogalactan was obtained. A degree of methylesterification (DE) of 71% and a degree of acetylation (DA) of 1.3% was determined by 1 H NMR spectroscopy and spectrophotometric quantification, respectively. A type I arabinogalactan was purified via Fehling precipitation and ultrafiltration through 50 kDa (cut-off) membrane. Its chemical structure was performed by sugar composition, HPSEC, methylation, carboxy-reduction and 13 C NMR spectroscopy analysis. Intraperitoneal administration of the arabinogalactan did not reduce the nociception induced by intraplantar injection of 2.5% formalin in mice, but significantly reduced the number of abdominal constrictions induced by 0.6% acetic acid, indicating that fraction has an antinociceptive effect on the visceral inflammatory pain model.